(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Preservation of our unique historical monuments, such as the architectural monument of the “Qirqqiz” Fortress is a sacred duty of every citizen living in the territory of Uzbekistan. After all, without historical and modern spirituality, without the development of enlightenment, it is impossible to build a state governed by the rule of law and civil society in our country. The article describes this.